Cost management : a strategic emphasis - Blocher, Edward; Stout, David Edward; Cokins, Gary (Boston : McGraw-Hill/Irwin, 2010)
The text is written to help students understand more about management and the role of cost accounting in helping an organization succeed. It addresses issues such as: cost management and cost systems,information for planning and process costing.
Includes index.
Keywords: Cost accounting; Managerial accounting